What contributes to alcohol and substance misuse recovery while parenting in integrated residential rehabilitation? : thesis submitted in partial completion of the requirements for the degree of Doctor of Clinical Psychology, Massey University, Auckland, New Zealand - Stanley, Laura (Massey University, 2023)
Alcohol and substance use recovery while parenting is a complicated endeavour. People in alcohol and substance misuse recovery while parenting have unique and complex needs, which mainstream treatment approaches cannot always meet. Treatment often focuses solely on substance misuse and fails to pay attention to parenting, and most often, parents and their children are separated during residential treatment. Parents often face the tough decision to either take care of themselves or take care of their children. Integrated treatment services, which include both drug and alcohol treatment and parenting support, have been developed to break the often intergenerational cycle of substance use and troubled parenting. These programmes have rendered successful outcomes in participants achieving and maintaining abstinence, improving their mental health, and supporting responsive parenting. However, little is known about what particular factors in integrated services support these positive changes made in recovery while parenting. The current research explores the unique factors that have contributed to parents’ recovery at the Family Centre, an integrated parent-child rehabilitation facility. The research additionally illustrates the needs of these individuals in recovery. Experiences of recovery and parenting were explored in semi-structured interviews and case studies with mothers undertaking a recovery programme. Through a reflexive thematic analysis, three themes were constructed: ‘The Construction of Self’ ‘The Therapeutic Milieu’, and ‘Relational Recovery’. The complex histories and recovery journeys of research participants were given context through the use of case vignettes. The findings highlight the complex and multifaceted nature of recovery while parenting, particularly the role that parenting plays in driving recovery-orientated change. The relational nature of recovery was a prevalent factor in recovery, providing a developing perspective on how recovery is viewed in research and practice.
Keywords: Parents; Alcohol use; Substance use; Alcoholics; Substance abuse; Patients; Rehabilitation; New Zealand; 520302 Clinical psychology